Body surface temperature adaptations after ice-cold water immersion in regular winter swimmers - Gruszka, K.; Jedrzejewski, G.; Sobiech, K. A.; Chwalczynska, A. (Biology of Exercise, 2018)
Background: the aim of the study was to compare the body surface temperature of regular winter swimmers before and after immersion in ice-cold water. Methods: the group studied comprised 20 male members of the club wroclawskie Morsy (of 38.1 +/- 1 2.6 years of age, body height 1.75 +/- 0.7 (m), body mass 77.2 +/- 10 (kg), bMI 25.1 +/- 2.8 (kg/m2) and body surface area 1.8 +/- 0.1 (m2)) who participated in 14 immersions during the winter swimmers` season. the experimental study consisted of a single sample of an approximately four-minute immersion in ice-cold water. the body surface temperature (anterior and posterior body side) distribution was registered with a thermographic camera (a20M) connected to the therma cam researcher 2.8 program. results: a decrease in temperature of 12 body areas was observed after the immersion, most significantly in the lower limbs and torso (60%). comparing the anterior and posterior body sides, a larger drop in temperature was noted in the frontal, less muscular area. conclusion: a correlation between the temperature of body surface areas before and after the immersion, dependent on the cooling environment (water/air), was established. The strongest association of the characteristics studied was observed in the lower limbs in the water environment. Application of thermovision in analysis of body surface temperature of regular winter swimmers was proved effective.